Pengaruh Social Environment, Religiosity dan Sharia Financial Knowledge Terhadap Minat Menggunakan Perbankan Syariah (Studi Kasus Pada UMKM Kabupaten Wonogiri) - Dewanti Wahyu Purwaningsih (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine whether social environment, religiosity dan sharia financial knowledge give an effect for the interest of Micro Small and Medium Enterprises (MSME), to use syariah banking in one of the district area at Central Java, namely Wonogiri. The method used in this study is a quantitative research with the random sampling technique. The number of the respondent who become sample was 400 MSME in Wonogiri district. The data of this study use likert scale parameters with Partial Least Square method (PLS) and analyze with using SmartPLS 3.0 Software. After doing examination, the findings obtained that Social Environment and sharia financial knowledge give positif and significant effect for the interest MSME using syariah banking. Sharia financial knowledge give the most contribution in affecting the interest UMKM use syariah banking with the result path coefficient 0,404, t-statistic 11,283 dan p-values 0, then social environment with the result path coefficient 0,358, t-satistic 9,694 dan p-values 0. However, it is different from religiosity which gives a negative influence and does not have a significant effect for the interest MSME in using syariah banking the value path coefficient -0,028, t-statistic 0,423 and p-values 0,673